Recursos didácticos en línea para el aprendizaje de electricidad y magnetismo en los estudiantes del primer año del bachillerato general unificado. - Merino Cueva, Juan Diego (2023)
Technological resources are increasingly used in education, therefore, the present research, aimed to characterize online didactic resources for learning Electricity and Magnetism. To this end, a study with a qualitative approach, documentary type and non-experimental design was proposed. It was used as research techniques, documentary analysis and signing; and as instruments, search logs and data record sheets. The main results show that these resources are important because they complement the teaching-learning process and the most appropriate according to their influence are: Proteus, EveryCircuit, DcAcLab, CircuitLab, ComPADRE and PSpice. Finally, although these resources favor the learning of Electricity and Magnetism, it is considered necessary to determine, quantitatively, this incidence, for which reason, an evaluation instrument was proposed to measure theoretical and practical knowledge based on a methodology based on these digital tools. Key words: technological resources, digital tools, learning physics, electricity and magnetism, physics simulators.